The K2 asteroseismic KEYSTONE sample of dwarf and subgiant solar-like oscillators: I. Data and asteroseismic parameters - Lund, Mikkel N.; Basu, Sarbani; Bieryla, Allyson; Casagrande, Luca; Huber, Daniel; Hekker, Saskia; Viani, Lucas; Davies, Guy R.; Campante, Tiago L.; Chaplin, William J.; Serenelli, Aldo M.; Ong, J. M. Joel; et al. (Astronomy and astrophysics, 2024)
Aims: The KEYSTONE project aims to enhance our understanding of solar-like oscillators by delivering a catalogue of global asteroseismic parameters (Δv and vmax) for 173 stars, comprising mainly dwarfs and subgiants, observed by the K2 mission in its short-cadence mode during campaigns 6–19. - Methods: We derive atmospheric parameters and luminosities using spectroscopic data from TRES, astrometric data from Gaia, and the infrared flux method (IRFM) for a comprehensive stellar characterisation. Asteroseismic parameters are robustly extracted using three independent methods, complemented by an iterative refinement of the spectroscopic analyses using seismic log g values to enhance parameter accuracy. - Results: Our analysis identifies new detections of solar-like oscillations in 159 stars, providing an important complement to already published results from previous campaigns. The catalogue provides homogeneously derived atmospheric parameters and luminosities for the majority of the sample. Comparison between spectroscopic Teff and those obtained from the IRFM demonstrates excellent agreement. The iterative approach to spectroscopic analysis significantly enhances the accuracy of the stellar properties derived.